Conversor CA-CA de elevado fator de potência para aplicações com geradores de Ímã permanente - Fernandes, Rodolfo C. [UNESP]; Godoy, Ruben B. [UNESP]; Melo, Guilherme A. [UNESP]; De Seixas, Falcondes J. M. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper proposes and describes a high power factor AC-AC converter for naval applications using Permanent Magnet Generator (PMG). The three-phase output voltages of the PMG vary from 260 Vrms (220 Hz) to 380 Vrms (360 Hz), depending on load conditions. The proposed converter consists of a Y-/ΔY power transformer, which provides electrical isolation between the PMG and remaining stages, and a twelve-pulse uncontrolled rectifier stage directly connected to a single-phase inverter stage, without the use of an intermediary DC-DC topology. This proposal results in more simplicity for the overall circuitry, assuring robustness, reliability and reduced costs. Furthermore, the multipulse rectifier stage is capable to provide high power factor and low total harmonic distortion for the input currents of the converter. The single-phase inverter stage was designed to operate with wide range of DC bus voltage, maintaining 120 Vrms, 60 Hz output. The control philosophy, implemented in a digital signal processor (DSP) which also contains protection routines, alows series connections between two identical converters, achieving 240 Vrms, 60 Hz total output voltage. Measured total harmonic distortion for the AC output voltage is lower than 2% and the input power factor is 0.93 at 3.6kW nominal load. © 2010 IEEE.
Keywords: AC-AC converters; DC-bus voltages; Electrical isolation; High power factor; Input current; Input power factor; Load condition; Multi-pulse rectifiers; Naval applications; Nominal loads; Output voltages; Permanent magnet generator; Reduced cost; Series connections; Single-phase inverters; Total harmonic distortions; Uncontrolled rectifiers; AC generator motors; DC power transmission; DC transformers; Digital signal processors; Electric equipment protection; Electric power factor correction; Harmonic distortion; Power transformers; Signal processing; Wave filters; Electric rectifiers